THE AGENCY RELATIONS AS A BASIS OF AN INSTITUTIONALIZATION OF THE MARKET OF THE STATE SERVICES IN RUSSIA - N. I. Larionova; I. N. Isupova (Модернизация, инновация, развитие, 2016)
In article the approach of provision of the state services on the basis of the agency relations is considered. Benefits of the agency relations in public administration in foreign countries are analyzed. The possible role of the state and participants of the market in creation of the agency relations on provision of the state services is studied. Possible risks of the agency relations in public administration are provided.